Supervisi tentang Komunikasi SBAR (Situation, Background, Assesmen and Recommendation) Berpengaruh terhadap Kualitas Handover Pasien di Ruang Rawat Inap Rumah Sakit - Sulistyawati, Wiwin; Haryuni, Sri (Universitas Tribhuwana Tunggadewi, 2019)
Ineffective handovers are often at high risk for patient safety. Other problems caused by improper handovers include delays in medical diagnosis, and increased health care costs and patient dissatisfaction. Supervision of SBAR communication (Situation, Background, Assessment, Recommendation) is an effective way to maintain patient safety and reduce the occurrence of errors caused by communication. This study aimed to identify the effect of supervision on SBAR communication on the quality of patient handovers in the inpatient room. Design research was a pre-experimental design of one group pre post test design, were 34 nurses in two inpatient rooms taken in total sampling. The SBAR supervision was carried out by the Head of the Room to the nurses during the handover. Before the supervision of nurses' handover quality was observed, then the socialization of SBAR communication and supervision by the head of the room were then given post-supervision observation. The instruments used a patient handover observation sheet and supervision manual. The results showed that most of the female respondents had D3 nursing education and half of the respondents had a working period of